Does Attendance Matter? An Examination of Student Attitudes, Participation, Performance and Attendance - Massingham, P.; Herrington, T. (Journal of University Teaching and Learning Practice, 2006)
Non attendance of lectures and tutorials appears tobe a growing trend. The literature suggests manypossible reasons including students’ changinglifestyle, attitudes, teaching and technology. Thispaper looks at the reasons for non attendance ofstudents in the Faculty of Commerce at theUniversity of Wollongong and identifies relationshipsbetween attendance, participation and performance.The results indicate that there are valid reasons fornon attendance that are both in the control oflearners and teachers. There are also clear benefitsfor students to be gained in attendance; however,changes in the way we learn, teach, assess and usetechnology are recommended if we wish to reversethe trend.